“You want the right amount of oversight”: interviews with data access committee members and experts on genomic data access - Shabani, Mahsa; Borry, Pascal (Genetics in medicine, 2016)
Purpose: Genomic data sharing is vital for optimizing the use of public-funded research data. Data access committees (DACs) have been introduced as a core component of governance in controlled-access models. However, the tasks, structure, and functionality of DACs often remain unstudied. This article investigates the role and adequacy of DACs in access reviews from the perspective of DAC members and experts. Methods: Twenty semi-structured interviews were conducted with both DAC members engaged in genomic data sharing via controlled-access databases and experts in the field. Results: The respondents indicated that protecting the privacy of data subjects along with recognition of data producers’ efforts are the main underlying reasons of access review and the controlled-access model. In reviewing the ethical basis and the scientific aspects of access requests, tools and mechanisms such as consent forms, data access agreements, and guidelines have been used. Nevertheless, DAC members and experts identified shortcomings associated with current approaches that may adversely impact the effectiveness and efficiency of access review. Conclusion: The identified shortcomings of current approaches to access review could be addressed via complementary mechanisms and alternative models of data sharing to facilitate access to data sets in a responsible fashion. Genet Med 18 9, 892–897.